2015
DOI: 10.5665/sleep.5066
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress is Prospectively Associated with Sleep in Midlife Women: The SWAN Sleep Study

Abstract: Chronic stress is prospectively associated with sleep disturbance in midlife women, even after adjusting for acute stressors at the time of the sleep study and other factors known to disrupt sleep. These results are consistent with current models of stress that emphasize the cumulative effect of stressors on health over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
115
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 51 publications
11
115
0
3
Order By: Relevance
“…37 Similarly, in a cross-sectional study of 8770 Japanese men and women, high occupational stress was significantly associated with *2-fold higher odds for insomnia in both men ( 38 Nevertheless, the Study of Women's Health Across the Nation Sleep Study, a US prospective study of 330 women, demonstrated that high chronic stress was associated with lower sleep quality (P < .001), increased insomnia (P < .001), and increased polysomnography-assessed wake after sleep onset (P < .01). 39 It is important to note that the association between sleep as well as other lifestyle behaviors and stress may be bidirectional and that observed gender differences in the influence of sleep on cardiovascular risk could alternatively be mediated by stress. 40…”
Section: Stress and Sleepmentioning
confidence: 99%
“…37 Similarly, in a cross-sectional study of 8770 Japanese men and women, high occupational stress was significantly associated with *2-fold higher odds for insomnia in both men ( 38 Nevertheless, the Study of Women's Health Across the Nation Sleep Study, a US prospective study of 330 women, demonstrated that high chronic stress was associated with lower sleep quality (P < .001), increased insomnia (P < .001), and increased polysomnography-assessed wake after sleep onset (P < .01). 39 It is important to note that the association between sleep as well as other lifestyle behaviors and stress may be bidirectional and that observed gender differences in the influence of sleep on cardiovascular risk could alternatively be mediated by stress. 40…”
Section: Stress and Sleepmentioning
confidence: 99%
“…One resource that has been largely understudied in the stress process is sleep quality. Despite previous research linking chronic stress and disrupted sleep quality (Hall et al, ; Pillai, Roth, Mullins, & Drake, ), as well as disrupted sleep quality and psychological distress (Goldstein & Walker, ), the role of sleep quality in promoting adjustment to chronic stress has been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…However, chronic stress , ongoing stressors lasting at least 1 year, has been related to a particularly high risk for insomnia (Pillai et al, ). In a 9‐year longitudinal study, exposure to chronic stress predicted poor subjective sleep quality and increased wake after sleep onset as assessed by polysomnography (Hall et al, ), indicating that the effects of stress on sleep may be particularly pronounced when the stress is chronic.…”
Section: Introductionmentioning
confidence: 99%
“…The Study of Women Across the Nation (SWAN) reported that midlife women (51.2±2.1 years) who showed a chronic stress profile characterized by more annual events that were “very and still upsetting” over a period of up to 9 years before a PSG study, had a poorer subjective sleep quality and more PSG-defined wakefulness, and were more likely to report insomnia than women with low or moderate stress profiles (Hall et al, 2015). These findings suggest that high levels of chronic stress may precipitate sleep continuity disturbances in midlife women (Hall et al, 2015).…”
Section: 1 Introductionmentioning
confidence: 99%
“…The Study of Women Across the Nation (SWAN) reported that midlife women (51.2±2.1 years) who showed a chronic stress profile characterized by more annual events that were “very and still upsetting” over a period of up to 9 years before a PSG study, had a poorer subjective sleep quality and more PSG-defined wakefulness, and were more likely to report insomnia than women with low or moderate stress profiles (Hall et al, 2015). These findings suggest that high levels of chronic stress may precipitate sleep continuity disturbances in midlife women (Hall et al, 2015). While Shaver and colleagues ( 2002 ) did not find a difference in perceptions of stress exposure in midlife women with and without insomnia, they found that the insomnia group had more psychological distress and a greater morning-evening difference in urine cortisol levels compared with controls.…”
Section: 1 Introductionmentioning
confidence: 99%